Tandem Metal Inert Gas process for high productivity Wire Arc Additive Manufacturing in stainless steel - Martina, Filomeno; Ding, Jialuo; Williams, Stewart W.; Caballero, Armando; Pardal, Goncalo; Quintino, Luísa (Elsevier, 2018)
This study investigates the feasibility of achieving high deposition rate using wire + arc additive manufacturing in stainless steel to reduce lead time and cost of manufacturing. The pulse MIG welding technique with a tandem torch was used for depositing martensitic stainless steel 17-4 PH. The mechanical and metallurgical properties of the manufactured component were analysed to evaluate the limitations and the extent to which the rate of deposition reaches a maximum without any failure or defect being evident in the manufactured component. Deposition rate of 9.5 kg/hr was achieved. The hardness was matched for the as deposited condition.
Keywords: Wire+arc additive manufacturing; martensitic stainless steel; high deposition rate